THE EFFECT OF PAPER DRYNESS TO THE NUMBER OF DRYING CYLINDER IN DRYING CYLINDERS - Yakut, Andac; Temir, Galip (YILDIZ TECHNICAL UNIV, 2012)
The most energy consuming section of the paper production facilities is the drying section. In general, the dryness of the paper at the entrance of the drying section is about 40 to 50%. If the degree of dryness of the paper entering the drying unit will be increased (moisture content will be decreased) energy savings can be achieved in drying unit. Shoe press units are used to improve the press effectiveness recently. In this study, it is observed that the number of drying cylinders can be reduced by 8 units according to our calculations when the dryness of the paper entering to the drying section of a paper production facility is increased from 49 to 55% with the desired degree of dryness.
Keywords: Paper drying; drying cylinders; dryness; energy savings; Engineering